The Cpx Envelope Stress Response Is Controlled by Amplification and Feedback Inhibition - Raivio, Tracy L. (American Society for Microbiology, 1999)
In Escherichia coli, the Cpx two-component regulatory system activates expression of protein folding and degrading factors in response to misfolded proteins in the bacterial envelope (inner membrane, periplasm, and outer membrane). It is comprised of the histidine kinase CpxA and the response regulator CpxR. This response plays a role in protection from stresses, such as elevated pH, as well as in the biogenesis of virulence factors. Here, we show that the Cpx periplasmic stress response is subject to amplification and repression through positive and negative autofeedback mechanisms. Western blot and operon fusion analyses demonstrated that the cpxRA operon is autoactivated. Conditions that lead to elevated levels of phosphorylated CpxR cause a concomitant increase in transcription of cpxRA. Conversely, overproduction of CpxP, a small, Cpx-regulated protein of previously unknown function, represses the regulon and can block activation of the pathway. This repression is dependent on an intact CpxA sensing domain. The ability to autoactivate and then subsequently repress allows for a temporary amplification of the Cpx response that may be important in rescuing cells from transitory stresses and cueing the appropriately timed elaboration of virulence factors.